Structural, electronic, optical and thermodynamic investigations of NaXF 3 (X = Ca and Sr): First-principles calculations - Benkabou, M.H.; Harmel, M.; Haddou, A.; Yakoubi, Abdelkader; Baki, N.; Ahmed, Rashid; Al-Douri, Yarub; Syrotyuk, Stepan V.; Khachai, Houari; Khenata, Rabah; Voon, Chun Hong; Johan, Mohd Rafie (Elsevier, 2018)
The structural, electronic and optical properties for fluoro-perovskite NaXF3 (X = Ca and Sr) compounds have calculated by WIEN2k code based on full potential linearized augmented plane wave (FP-LAPW) approach within density functional theory (DFT). To perform the total energy calculations, exchange-correlation energy/potential functional has been utilized into generalized gradient approximation (GGA) and local density approximation (LDA). Our evaluated results like equilibrium lattice constants, bulk moduli, and their pressure derivatives are in agreement with the available data. The electronic band structure calculation has revealed an indirect band-gap nature of NaCaF3, while NaSrF3 has direct band gap. Total and partial densities of states confirm the degree of localized electrons in different bands. The optical transitions in NaCaF3 and NaSrF3 compounds were identified by assigning corresponding peaks obtained from the dispersion relation for the imaginary part of the dielectric function. The thermodynamic properties were calculated using quasi-harmonic Debye model to account lattice vibrations. In addition, the influence of temperature and pressure effects was analyzed on bulk modulus, lattice constant, heat capacities and Debye temperature.